Immunological and Biological Manifestation of Rheumatoid Arthritis Patient in Iraq - RusulH.Ahmad; AyaidK.Zgair (Institute of Medico-legal Publications Pvt Ltd, 2021)
Rheumatoid arthritis is one of the highly incidence autoimmune disease. In present study the immunologicaland clinical biochemical test was checked in patients with RA in Iraq. Here 70 serum specimens wereobtained from patients suffer from RA and 30 serum specimens from healthy control cohorts. Antinuclearantibodies (ANA) level, C-reactive protein level, erythrocyte sedimentation rate (ESR), activity of alanineaminotransferase (ALT), activity of aspartate aminotransferase (AST), concentration of blood urea andserum creatininand diseases activity score (DAS)-28 were evaluated in sera of patients and healthy controlcohorts. The results showed that significant elevation in level of ANA, ESR, CRP and DAS-28 in patientsgroup as compared to healthy control group (P<0.05). No significant difference between patients group andhealthy control group in terms of activity of ALT, AST, concentration of blood urea and serum creatinine.The person test (r) was done to evaluate the correlation between ESR, ANA, CRP, ALT, AST, blood urea andserum creatinine. The results showed significant relation between levels of ESR, CRP and ANA and activityof disease in terms of DAS-28. The results showed no significant relation between level of CRP, ALT, AST,blood urea and serum creatinine in patient’s sera and DAS-28. It can be concluded from present study thatthe some laboratory parameters related with activity of RA such as ESR, ANA, CRP and other parametersdo not related with activity of RA such asALT, AST, blood urea and serum creatinine.